Depiction restoring women’s power through eatery names - Ananta Tur, Ajar Pradika; Sabrina, Arini; Noor, Azelin Mohamed; Farahsani, Yashinta; Puspita, Ida; Kurniawan, Muhammad Hafiz (UI Scholars Hub, 2023)
Empowering women entails bolstering their mentality and state of mind, as patriarchy is founded not only on sexuality. Addressing a married woman with the name of her husband or first son is claimed to be a sign of respect. Woman’s public inclusion is also still considered undervalued, which is shown in the way they name eateries. This study, which unfolds eatery names in Yogyakarta Municipality in Indonesia and Malacca in Malaysia, two places with identical historical backgrounds, analysed women’s efforts to increase their bargaining position in society through the naming of their eateries. Although two eateries do place women in a strong position, many of them still struggle to achieve women’s positionalities and social respect.